Cortical thickness is not associated with current depression in a clinical treatment study. Issue 9 (8th June 2017) - Perlman, Greg; Bartlett, Elizabeth; DeLorenzo, Christine; Weissman, Myrna; McGrath, Patrick; Ogden, Todd; Jin, Tony; Adams, Phillip; Trivedi, Madhukar; Kurian, Benji; Oquendo, Maria; McInnis, Melvin; et al.
Abstract: Background: Reduced cortical thickness is a candidate biological marker of depression, although findings are inconsistent. This could reflect analytic heterogeneity, such as use of region‐wise cortical thickness based on the Freesurfer Desikan–Killiany (DK) atlas or surface‐based morphometry (SBM). The Freesurfer Destrieux (DS) atlas (more, smaller regions) has not been utilized in depression studies. This could also reflect differential gender and age effects. Methods: Cortical thickness was collected from 170 currently depressed adults and 52 never‐depressed adults. Visually inspected and approved Freesurfer‐generated surfaces were used to extract cortical thickness estimates according to the DK atlas (68 regions) and DS atlas (148 regions) for region‐wise analysis (216 total regions) and for SBM. Results: Overall, except for small effects in a few regions, the two region‐wise approaches generally failed to discriminate depressed adults from nondepressed adults or current episode severity. Differential effects by age and gender were also rare and small in magnitude. Using SBM, depressed adults showed a significantly thicker cluster in the left supramarginal gyrus than nondepressed adults ( P = 0.047) but there were no associations with current episode severity. Conclusions: Three analytic approaches (i.e., DK atlas, DS atlas, and SBM) converge on the notion that cortical thickness is a relatively weak discriminator of current depression status. Differential age and gender effects do not appear to represent key moderators. Robust associations with demographic factors will likely hinder translation of cortical thickness into a clinically useful biomarker. Hum Brain Mapp, 2017 . ©2017 Wiley Periodicals, Inc . Hum Brain Mapp 38:4370–4385, 2017 . ©2017 Wiley Periodicals, Inc.